Phenotypic switching of vascular smooth muscle cells in atherosclerosis, hypertension, and aortic dissection - Mohamed Elmarasi (14614276) (2024)
Vascular smooth muscle cells (VSMCs) play a critical role in regulating vasotone, and their phenotypic plasticity is a key contributor to the pathogenesis of various vascular diseases. Two main VSMC phenotypes have been well described: contractile and synthetic. Contractile VSMCs are typically found in the tunica media of the vessel wall, and are responsible for regulating vascular tone and diameter. Synthetic VSMCs, on the other hand, are typically found in the tunica intima and adventitia, and are involved in vascular repair and remodeling. Switching between contractile and synthetic phenotypes occurs in response to various insults and stimuli, such as injury or inflammation, and this allows VSMCs to adapt to changing environmental cues and regulate vascular tone, growth, and repair. Furthermore, VSMCs can also switch to osteoblast‐like and chondrocyte‐like cell phenotypes, which may contribute to vascular calcification and other pathological processes like the formation of atherosclerotic plaques. This provides discusses the mechanisms that regulate VSMC phenotypic switching and its role in the development of vascular diseases. A better understanding of these processes is essential for the development of effective diagnostic and therapeutic strategies. Other Information Published in: Journal of Cellular Physiology License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1002/jcp.31200